Socialization of Organic Waste Processing in the Lembar Selatan Mangrove Ecotourism Area, West Lombok - Ernawati; Suripto; Kamali, Siti Raudhatul; Widianti, Astrini; Rahayu, Rachmawati Noviana; Assyifa, Baiq Tiara Wimadhia (Universitas Mataram, 2024)
In ecotourism areas, tourist activities are always a source of waste generation. Tourist visits can have a positive impact on the community's economy, but they also have a negative impact, namely increased waste generation. The Lembar Selatan Mangrove Ecotourism Area is an ecotourism destination in West Lombok which attracts more and more visitors from year to year. The increase in the number of visitors causes an increase in waste generation in tourist areas. Some rubbish is still dumped in mangrove forests, so a lot of rubbish is found in mangrove forests which are ecotourism objects. Integrated waste management is needed, especially through empowering local communities to overcome the problem of waste generation in the area. For this reason, socialization of waste processing into eco-enzyme products for the community was carried out with the aim of increasing awareness and economic independence of the community in managing waste. This socialization was carried out using lecture methods, demonstrations, focus group discussions and practice with female food traders who are members of the UMKM group and members of POKDARWIS of The Lembar Selatan Village as the target audience. The results show that the participants were very enthusiastic about taking part in this activity, causing their awareness, knowledge and skills to increase, especially regarding integrated waste management and processing organic waste into eco-enzyme products. It is hoped that the results of this activity will further increase the village's economic independence in managing waste in the Ecotourism Area of Lembar Selatan.